2018
DOI: 10.1101/314351
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geographic variation in adult and embryonic desiccation tolerance in a terrestrial-breeding frog

Abstract: ABSTRACTIntra-specific variation in the ability of individuals to tolerate environmental perturbations is often neglected when considering the impacts of climate change. Yet this information is potentially crucial for mitigating any deleterious effects of climate change on threatened species. Here we assessed patterns of intra-specific variation in desiccation tolerance in the frog Pseudophryne guentheri, a terrestrial-breeding species experiencing a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 93 publications
(100 reference statements)
1
5
1
Order By: Relevance
“…Variation within the genic region of PKC zeta may be associated with differential expression of the PKC zeta gene (Liu et al, 2004) threatened, our analysis reveals genetic patterns consistent with population isolation, decline and inbreeding, suggesting the species is at greater risk of extinction than is currently recognized. We provide strong molecular evidence of local adaption, which is supported by a parallel study of P. guentheri that found strong patterns of clinal variation in desiccation tolerance (both in adults and firstgeneration offspring) across a rainfall gradient (Rudin-Bitterli, 2018).…”
Section: Signatures Of Local Adaptationsupporting
confidence: 70%
See 3 more Smart Citations
“…Variation within the genic region of PKC zeta may be associated with differential expression of the PKC zeta gene (Liu et al, 2004) threatened, our analysis reveals genetic patterns consistent with population isolation, decline and inbreeding, suggesting the species is at greater risk of extinction than is currently recognized. We provide strong molecular evidence of local adaption, which is supported by a parallel study of P. guentheri that found strong patterns of clinal variation in desiccation tolerance (both in adults and firstgeneration offspring) across a rainfall gradient (Rudin-Bitterli, 2018).…”
Section: Signatures Of Local Adaptationsupporting
confidence: 70%
“…On this basis, higher levels of inbreeding would be expected in our populations near the northern range edge, yet we observed the opposite pattern. Alternatively, the differences could arise via kin selection in southern populations, or due to differing levels of multiple mating, as implied by marked divergence of male reproductive traits in these same populations (Rudin-Bitterli, 2018), and recognition of complex and variable mating systems in congeners (O'Brien et al, 2018). Alternatively, the differences could arise via kin selection in southern populations, or due to differing levels of multiple mating, as implied by marked divergence of male reproductive traits in these same populations (Rudin-Bitterli, 2018), and recognition of complex and variable mating systems in congeners (O'Brien et al, 2018).…”
Section: Isolation and Inbreedingmentioning
confidence: 99%
See 2 more Smart Citations
“…This is contrary to our prediction, as smaller salamanders are expected to have higher rates of water loss per unit area [23]. While studies have found evidence for geographic variation in desiccation resistance indicative of local adaptation based on gradients of environmental moisture e.g., [82,83] it is notable that we did not find evidence for plasticity in resistance to water loss based on our moisture treatments. This result has important implications for the ability of salamanders to respond to changes in environmental moisture.…”
Section: Discussioncontrasting
confidence: 57%